Diseño del Hostal “MONTAÑITA”, mediante la elaboración del plan de negocios para fortalecer el turismo en la Parroquia Tarapoa, Cantón Cuyabeno, Provincia de Sucumbíos - Mora García, Mireya Marisol (2018)
Tourism in the province of Sucumbíos has become a very important source of foreign currency income either for national or foreign tourists, since the Canton Sucumbíos is known for being the northern gate of the Amazon, since few places in the The world has great natural wealth and an extraordinary biodiversity worthy of knowing it. Thus, Cuyabeno is considered an intangible territory since it is within the Fauna Production Reserve, having innumerable places of great tourist potential, considered as the first ecological canton of the Province. Being a tourist place of greater relevance in the Amazon it is necessary to have the necessary infrastructure to offer a quality service to tourists. Therefore, it is necessary to carry out studies that are related to the implementation of tourism infrastructure in this case the "DESIGN OF THE HOSTEL "MOUND", THROUGH THE DEVELOPMENT OF THE BUSINESS PLAN TO STRENGTHEN TOURISM IN THE PARISH TARAPOA, CANTON CUYABENO," ' PROVINCE OF SUCUMBIOS ' The materials used were useful office and office equipment, the methods that were applied to the research are: deductive, inductive, analytical, synthetic, descriptive, statistical analysis, which allowed the development of the different studies of the project; Likewise, some techniques were used, such as the collection of primary information, the survey that was applied to national and foreign tourists, the interview that was conducted with managers of establishments with a similar type of service; and, that of secondary information that was obtained from the different bibliographic review that allowed to base the investigation The results with respect to the market study, showed that there is unmet demand that can be used for the implementation of the project; the technical study that allowed to determine the size and the optimal location, as well as the engineering of the project and the organic-functional structure. The economic-financial analysis was carried out, where the Project Investment was determined, which was $ 246,784.71, this investment will be financed 68% with a loan to BanEcuador and 32% with the contribution of the partners; Likewise, the elaboration of the cost and income budgets that allowed the analysis of the equilibrium point and the Profit and Loss Statement were made. 5 The Financial Evaluation produced positive results, determining that the project is feasible: The Net Present Value, gave a value of $. 653.559.54, said value being greater than the investment; the Internal Rate of Return that is equivalent to 34.43% that is greater than the opportunity cost; the capital that will be recovered in 3 years, 10 months and 22 days; When the hostel is implemented, two dollars of profitability will be obtained for each dollar invested; Likewise, it was determined that the project supports an increase in costs of 85% and a decrease of 29.80% in costs. Therefore, investors from the Province, Guangzhou and Provincial and Municipal Authorities are recommended to carry out an analysis of the results of the project and can be carried out.